1984
DOI: 10.1080/00015128409436178
|View full text |Cite
|
Sign up to set email alerts
|

Source of Nitrogen for Rumen Microbes

Abstract: In vitro technique was used to elucidate the effect of different nitrogen sources on the growth of rumen microbes. The results showed that the digestibility of cellulose with soybean and casein as nitrogen source mas higher than all other nitrogen sources used in this experiment. The digbestibility of cellulose with polypeptides as nitrogen source was higher than with glutathione, casein hydrolysate,, amino acid mixture and urea. The digestibility of cellulose with urea mas very low for all levels of nitrogen.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Supplementation with U or SM stimulated TSDOC fermentation, as shown by the increase of daily VFA production and efficiency (by 1.6 and 2.8 and 1.2 and 2.0 times, respectively). The results obtained with TSDOC agreed with those of other authors, who found a higher stimulating effect on the fermentation when supplementing with NAN, in comparison with ammonia N [9,16,26,31]. The increased acetate production with PEG treatment would indicate an increased fermentation of TSDOC carbohydrates, in agreement with other observations [6,37].…”
Section: Discussionsupporting
confidence: 83%
“…Supplementation with U or SM stimulated TSDOC fermentation, as shown by the increase of daily VFA production and efficiency (by 1.6 and 2.8 and 1.2 and 2.0 times, respectively). The results obtained with TSDOC agreed with those of other authors, who found a higher stimulating effect on the fermentation when supplementing with NAN, in comparison with ammonia N [9,16,26,31]. The increased acetate production with PEG treatment would indicate an increased fermentation of TSDOC carbohydrates, in agreement with other observations [6,37].…”
Section: Discussionsupporting
confidence: 83%
“…Protozoa have been reported to increase the turnover of bacterial protein in rumen fluid 13-fold (Wallace and McPherson 1987), with much of the catabolized protein being released as peptides (Denholm and Ling 1985). Huque and Thomsen (1984) and Thomsen (1985) have demonstrated that low polypeptide availability may limit the rate of cellulolysis by rumen microbes in-vitro. The higher rate of fermentation in the rumen of faunated sheep may therefore result from a greater availability of polypeptides for use by cellulolytic bacteria in the rumen, as well as from the action of protozoal cellulases in these animals.…”
Section: Rumen Fermentationmentioning
confidence: 99%
“…These become activated only gradually after feeding, because they must first attach themselves to plant material (Mertens, 1977), and because the pH has not yet reached an optimum level for this activity. According to Huque & Vestergaard Thomsen (1984) cellulolytic microbes prefer certain polypeptides, as a nitrogen source. The availability of these polypeptides about three hours after the intake of concentrate protein is more likely on a feed with slowly degradable protein.…”
Section: Ammoniamentioning
confidence: 99%